Performance evaluation of ATM multiplexer with batch arrivals in ATM networks - 241980 Mohd. Zefri Salleh (Kuala Lumpur : UTM, 1994)
Due to the increased demand for communication services of all kinds such as voice, data, text and video, Broadband Integrated Services Digital Network (B-ISDN) has received increased attention in the past few years. Among the techniques proposed to implement B-ISDN, Asynchronous Transfer Mode (QTM) is considered to be the most promising transfer technique because of its efficiency and flexibility. B-ISDN currently is defined for ATM transport mapped into a SONET (Synchronous Optical Network) fober optics facilities. Due to the bursty nature of some services, congestion will occurs in some parts of the network such as in the ATM multiplexer of switching nodes. Various kinds of traffic which are carried in the ATM network have different characteristics. Some traffic carries in batches such as voice cells which are packetized into two priorities - high and low priority. During congestion, the low prioority cells can be discarded if being given the choice. Thus, the quality of voice can be maintained. Such queueing system are analyzed using an adaptive differential pulse code modulation (ADPCM) technique to include in this scheme called selective cell discarding (SCD). This thesis is intended to study the performance evaluation of ATM multiplexer in batch arrivals in ATM networks using simulation approach (SIMSCRIPT II.5 simulation package). Firstly , a survey of the existing preformance evaluation schemes is presented. Theccontributions of the thesis are as follows : The thesis investigations the performance evaluation of an ATM multiplexer under traffic congestion. Finally, the author developed the simulation model and to examine the delay and loss performance of an ATM multiplexer. The results from simulation process is presented ing raph patterns for cells loss rate and cell delay versus data load offered (Pd).